Crops, crop pests and climate change – why Africa needs to be better prepared - Smith, Julian (2015)
Ongoing investments in agriculture will not deliver for Africa until the destabilising nature of crop pest1 events, especially shock outbreak events, are addressed. As a result of climate change, the prevalence of crop pests will change and the frequency of shock pest events will increase, putting agricultural systems at risk. The granularity of these changes, in terms of choices by farmers, cropping systems and markets, presents a critical challenge.